The Effects of Work Ability, Level of Coordination and Work Motivation on the Success of the Government's Food Reserve (GFR) Program in Bengkulu City - Sari, Sri Novita; Aminudin, Achmad; Suratman (Future Science, 2024)
The Government Food Reserve (GFR) program is a strategic step in ensuring food availability throughout Indonesia, managing price volatility, and dealing with the impact of natural and social disasters. In Bengkulu City, the successful implementation of the GFR has a very significant impact given the similar challenges faced by other regions in Indonesia. The success of the GFR program in Bengkulu City is influenced by three key factors: work ability, level of coordination, and motivation of the program implementers. Therefore, this study aims to analyze the influence of these three factors on the success of the GFR program in Bengkulu City. The census method was used, targeting GFR program implementers at the kecamatan, village/kelurahan, dusun, and RT levels. Data was collected through a survey with a questionnaire designed to measure the variables of work ability, coordination level, work motivation, and GFR program success. The results showed that there is a significant influence of work ability, coordination level, and work motivation on the success of GFR program in Bengkulu City. The support from these three factors allows the GFR program to maintain food availability for the community effectively and efficiently. Hard work and integration of related agencies are the main keys in achieving the objectives of the GFR program, providing a positive impact on social and economic stability in Bengkulu City.